TPACK Implementation assisted by Interactive Multimedia Games based on increasing active participation and social study Learning Outcomes of students 4 Abu Bakar Ash Shiddiq - Yuli Setioningrum (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research is based on the author's observations on the participation and achievement of students who tend to decline during the online learning process during the pandemic. The purpose of this research is to produce digital-based learning media that is fun for students, practical and efficient for the teacher, and to find out the effect of the implementation of TPACK assisted by Interactive Multimedia Games on increasing participation and learning outcomes of students. The research implementation will be divided into two stages, namely research planning and research implementation starting in October 2020 for planning and implementation in November  2020 in class 4 Abu Bakar Ash Shiddiq. The results showed that the implementation of TPACK assisted by interactive multimedia games had an effect on active participation and social studies learning outcomes of students. The active participation of students increased in cycle 1 by 73.07% to 92.30% in cycle 2, the last cycle incrreased 100%. Students' social studies learning outcomes also increased. The percentage of students who reached the KKM in cycle 1 was 57.69% , 100% in cycle 2, the last cycle stable 100%.